2014
DOI: 10.1177/1541931214581178
|View full text |Cite
|
Sign up to set email alerts
|

The effects of automation-induced complacency on fault diagnosis and management performance in process control

Abstract: Operators of automated systems can develop complacency, impairing their ability to respond in a timely and appropriate fashion when automation fails. This study sought to examine the impact of an instructional manipulation of attentiveness, in terms of engagement and accountability, on fault diagnosis and fault management. Participants trained on the operation of a simulated process control task, with instructions varied to induce higher or lower attentiveness to the task. After several routine faults within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…To address the objective of evaluating FFs of decision aiding across automation failure types, in the current experiment in a between-subjects design, three groups of participants managed AutoCAMS 2.0, the microworld process control simulation employed by Bahner et al (2008), Manzey et al (2012), and Clegg, Vieane, Wickens, and Sebok (2014). Operators managed a series of trials in AutoCAMS during which they experienced a series of "routine system malfunctions" (e.g., stuck valves that could be diagnosed and fixed using procedures).…”
Section: Introductionmentioning
confidence: 99%
“…To address the objective of evaluating FFs of decision aiding across automation failure types, in the current experiment in a between-subjects design, three groups of participants managed AutoCAMS 2.0, the microworld process control simulation employed by Bahner et al (2008), Manzey et al (2012), and Clegg, Vieane, Wickens, and Sebok (2014). Operators managed a series of trials in AutoCAMS during which they experienced a series of "routine system malfunctions" (e.g., stuck valves that could be diagnosed and fixed using procedures).…”
Section: Introductionmentioning
confidence: 99%
“…This effect was found to be well supported in a meta-analysis to investigate the effects of degree of automation on operator performance (Onnasch et al, 2013).  Cognitive complexity: we are currently performing targeted HITL experimentation to gather data to support and quantify this intuitively obvious effect (Clegg, Vieane, et al, 2014). From informal observations with the AutoCAMS environmental process control simulation, we have found that participants experience the greatest difficulty in diagnosing the most complex (i.e., mixer system) failures.…”
Section: Hai Effects On Diagnosismentioning
confidence: 82%
“…In the active management, unlike known problems, the problem management system must identify the effect of defect components in accordance to the fault diagnosis results [3]. Then the available functions are determined by the problem management system.…”
Section: Introductionmentioning
confidence: 99%